2013
DOI: 10.1074/jbc.m112.445551
|View full text |Cite
|
Sign up to set email alerts
|

The Hyaluronic Acid Receptor CD44 Coordinates Normal and Metaplastic Gastric Epithelial Progenitor Cell Proliferation

Abstract: Background: Gastric parietal cell atrophy causes metaplasia, reactive stem cell proliferation, and increased risk for cancer. Results: Atrophy induces proliferation of CD44-positive epithelial cells that requires ERK 3 CD44 3 STAT3 signaling. Conclusion: CD44 is a putative gastric stem cell marker that regulates normal and metaplasia-associated proliferation. Significance: Targeted pharmacological inhibition of ERK/CD44/STAT3 signaling may help block or reverse proliferation in precancerous atrophic/metaplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 76 publications
9
109
1
Order By: Relevance
“…CD44 together with other oncoproteins, such as MMP-2 and MMP-9, have been reported to be associated with gastric cancer metastasis (27). Khurana et al recently documented that loss of CD44 in vivo results in decreased proliferation of gastric epithelium and the ERK→CD44→STAT3 signaling pathway regulates normal and atrophy-induced gastric stem/progenitor-cell proliferation (28). Additionally, lines of evidence suggest that MMPs participate in cell growth, angiogenesis and epithelial-mesenchymal transition (3).…”
Section: Discussionmentioning
confidence: 99%
“…CD44 together with other oncoproteins, such as MMP-2 and MMP-9, have been reported to be associated with gastric cancer metastasis (27). Khurana et al recently documented that loss of CD44 in vivo results in decreased proliferation of gastric epithelium and the ERK→CD44→STAT3 signaling pathway regulates normal and atrophy-induced gastric stem/progenitor-cell proliferation (28). Additionally, lines of evidence suggest that MMPs participate in cell growth, angiogenesis and epithelial-mesenchymal transition (3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 80% of eR1 Additional markers have been proposed for gastric stem cells (e.g., DCKL1/DCAMKL1, CD133/PROM1, and CD44), but the multipotency of these cells has not yet been analyzed by lineage tracing [15,16]. Khurana et al found that CD44 (cluster of diferentiation 44) is mainly expressed at the base of antral/pyloric glands, in a region overlapping Lgr5, and in the isthmus region of the corpus glands [17,18]. When parietal cell loss and atrophy were induced chemically or by Helicobacter infection, the CD44 + cells expanded from the isthmus and replenished the base of the gastric units (Figure 2).…”
Section: Discovery Of Gastric Stem Cells and Their Markersmentioning
confidence: 99%
“…Interestingly, the parietal cell atrophy induced after H. pylori infection causes an increase in the proliferation of stem/progenitor cells in the isthmus [37] that is associated with an induction of CD44 expression in this region, which then expands toward the botom of the gastric unit [17,35,36] (Figure 2). Sigal et al also reported an increase of the number of antral Lgr5 + cells in H. pylori-associated gastritis and carcinoma in humans.…”
Section: Tumors Can Originate From Epithelial Stem Cell Transformationmentioning
confidence: 99%
See 2 more Smart Citations